Humphrey 자동시야계를 이용한 한국인의 정상시야 - 임성준; Sung Jun Lim; 이주화; Joo Hwa Lee (Daihan angwa haghoi jabji, 1998)
정상 한국인 62명(124안)에게 Humphrey 자동시야계를 이용하여 30-2 중심시야역치검사 (Central 30-2 threshold test)를 시행하여 검사치를 제시함으로써 향후 임상적으로 녹내장의 진단에 도움을 주고, 시야 관찰의 기초 자료로 사용되도록 하였다. 측정치의 평균값은 중심와역치(Foveal threshold)가 34.3±2.6㏈, mean deviation (MD)이 -1.96±1.31㏈, pattern standard deviation(PSD)이 2.25±0.88㏈, short-term fluctuation(SF)이 1.38±0.52㏈, corrected pattern standard deviation(CPSD)이 1.41±1.10㏈으로 나타났다. 시야검사계에서 정한 정상 범위를 벗어난 경우(p<5%)는 중심와역치가 25.5%, MD이 19.1%로 높게 나타났으며, PSD, SF, CPSD는 큰 차이를 보이지 않았다. 상관관계 분석에서는 연령이 증가할수록 중심와역치는 낮아지고(r=-0.729), PSD와 CPSD는 높아지는 (r=0.422, 0.385) 통계학적으로 유의한 상관관계를 보였다(p<0.05). 본 연구는 시야검사를 1회만 시행하였고 대상안이 적다는 제한이 있으며, 이에 대해서는 추후반복검사에 따른 비교분석 및 더 많은 대상안을 포함한 연구가 필요할 것으로 사료된다(한안지39:1499~1504, 1998). Central 30-2 threshold tests were performed in 124 eyes of 62 normal subjects with Humphrey Field Analyzer. The average value of foveal threshold, mean deviation(MD), pattern standard deviation(PSD), shor-term fluctuation(SF) and corrected pattern standard deviation(CPSD) were 34.3±2.6dB, -1.96±1.31dB, 2.25±0.88dB, 1.38±0.52dB and 1.41±1.10dB, respectively. The frequency of abnormal value on automated perimetry(p<5%) was 25.5% in foveal threshold and 19.1% in MD, which was higher than fundamental data of perimetry. As the age increased, foveal threshold decreased (r=-0.729), PSD and CPSD increased (r=0.422) and 0.385, respectively) ; these are statistically significant correlations(p<0.05). This study has the limitation that test was performed on single session and had small study group. Therefore, further study is needed with comparative analysis following repeated test and larger group of visual field examination(J Korean Ophthalmol Soc 39:1499~1504, 1998).